«DON'T OPPOSE THE EVIL TO GET INTO YOU …» (ABOUT NONRESISTANCE TO THE EVIL BY FORCE: TOLSTOY, SOLOVJEV, VOLOSHIN, STEINER) - T. A. Koshemchuk (Концепт: философия, религия, культура, 2018)
The article deals with the theory of the evil in life and creativity of M. Voloshin. His position is analyzed in connection with Tolstoy’s nonresistance to the evil as the result of its reconsideration and in connection with criticism of nonresistance by V. Solovyov. It is shown that Voloshin’s position is defined by its creative development of R. Steiner’s concept of world history. His personality had the defining influence on development of Voloshin’s position in the years of revolution - as protection of the person against the crowd, whether it is red or white. Voloshin’s approach to the person inspired by the evil for the sake of saving of lives is investigated – as it is reflected in his verses, articles and letters. Actions of the poet were based on his taking the evil in world history as real, operating in the world force. According to Steiner, the spirits of the evil were initially spirits of obstacles for the sake of human development, but during history as a result of karmic regularities became the real evil, and rescue of the evil lies in the field of responsibility of the Man. From here the main Voloshin’s idea – which is taken out in the title of the article – is about acceptance of the evil into the soul and of its transformation into the good. Possibility of this transformation is defined by a lack of ontologic division between the evil and the good. Creativity of the person thereby appears in the field of realization of forms. This Voloshin’s position became a basis of his vital activity during the period of revolution and terror – in saving of human lives.